Does Industrial Air Pollution Increase Health Care Expenditure? Evidence From China - Shen, Jin-Sheng; Wang, Qun; Shen, Han-Pu (Frontiers in Public Health, 2021)
This paper discusses the impact of air pollution on medical expenditure in eastern, central and western China by applying the fixed-effect model, random effect model and panel threshold regression model. According to the theoretical and empirical analysis, there are different relationships between the two indexes in different regions of China. For eastern and central regions, it is obvious that the more serious the air pollution is, the more medical expenses are. However, there is a nonlinear single threshold effect between air pollution and health care expenditure in the western region. When the air pollution is lower than this value, there is a negative correlation between them. Conversely, the health care expenditure increase with the aggravation of air pollution, but the added value is not enough to make up for the health problems caused by air pollution. The empirical results are basically consistent with the theoretical analysis, which can provide enlightenment for the government to consider the role of air pollution in medical expenditure. Policymakers should arrange the medical budget reasonably according to its situation, to make up for the loss caused by air pollution.